Peningkatan Kreativitas Siswa Kelas XI Melalui Penerapan Metode Pemberian Tugas di SMK Negeri 2 Palopo - Muh. Arifin Abbas (Celebes Engineering Journal, 2019)
This research is a Classroom Action Research that aims to increase student creativity in subjects drawing lighting installation plans through the method of giving individual assignments to class XI Electric Power Installation Techniques 2014/2015 Academic Year, with the number of students as a sample of 20 student people. The implementation of face-to-face in this research is, in Cycle I held two meetings and in cycle II only one meeting. Data collection techniques used were observation, essay test and practice assessment. The data analyzed is using qualitative analysis. The results of research conducted from August to October 2014 show that (1). Students' attitudes toward learning that are done increase by seeing changes in student attitudes and student behavior both in cycle I and in Cycle II, (2). Mastery of learning materials in the first cycle is in the medium category by looking at the average score of students is 79.20, while in Cycle II has shown a significant change in the acquisition of scores with the acquisition of an average score of 84.16, which means it is in the high category. Based on the results of this study, it can be concluded that the application of the assignment method is quite effective to increase students' creativity in class XI of the Electric Power Installation Engineering Program at SMK Negeri 2 Palopo.